Non-adherence to medication, malaria relapse, and asymptomatic reservoirs in malaria transmission: A narrative review - Sahiddin, Muhamad; Ishak, Hasanuddin; Arsin, Andi Arsunan; Mallongi, Anwar; Arsyad, Muhammad; Hamid, Firdaus (Public Health of Indonesia, 2025)
Background: Malaria elimination remains a pressing global health priority, yet progress is hindered by interconnected human-driven factors that sustain residual transmission. Objectives: This review aims to integrate and analyze key factors driving residual malaria transmission, particularly non-adherence to anti-malarial medication, relapse of Plasmodium vivax and P. falciparum infections, and the persistence of asymptomatic parasite reservoirs. Methods: A narrative review was conducted by synthesizing findings from peer-reviewed studies, including observational studies, clinical trials, and program evaluations. Relevant articles were identified through PubMed, Scopus, Google Scholar, and Web of Science databases. Results: Demographic, behavioral, and health system factors were consistently associated with incomplete treatment, which in turn doubled relapse risk and extended the duration of gametocyte carriage. Biological factors, such as dormant hypnozoites and CYP2D6 polymorphisms that reduce primaquine metabolism, increased the likelihood of recurrent infections. Additionally, asymptomatic carriers disproportionately younger and mobile populations sustained transmission beyond the reach of routine surveillance. Unlike previous reviews that examined these factors separately, this review integrates them into a unified framework, emphasizing their synergistic effects on residual transmission and identifying leverage points for targeted interventions. Conclusion: Addressing residual malaria transmission requires coordinated strategies, including community-supervised or directly observed radical cure regimens, genotype-informed dosing strategies, molecular surveillance for asymptomatic infections, and culturally tailored adherence support. These interventions are essential to strengthen malaria elimination programs and advance progress toward national and global goals by 2030. Keywords: adherence medication; relapse; transmission; endemic; malaria